(untitled) (Health Renaissance, 2014)
Acute angle closure glaucoma (AACG) can be induced by topical mydriatics which are used as cycloplegic and to prevent synechiae while treating corneal ulcer disease. Development of AACG in opposite eye by use of topical mydriatic in one eye is a very rare condition. We report a very rare case of a 45-year-old male who while using topical atropine in the right eye for corneal ulcer developed atropine induced AACG in the left. The AACG in this patient was managed by medications and laser iridotomy followed by trabeculectomy. The aim of this case report is to raise the awareness about this rare adverse effect of topical use of atropine where AACG can be induced in contralateral eye which warrants the clinician to be more careful and vigilant while prescribing atropine so that timely intervention can prevent the devastating condition leading to blindness. DOI: http://dx.doi.org/10.3126/hren.v11i3.9658 Health Renaissance 2013;11(3):290-292